RETRACTED: Review of studies on the use of synbiotic feed additives in compound feeds - Rudoy Dmitry; Pakhomov Victor; Maltseva Tatyana; Olshevskaya Anastasiya; Sarkisian Dzhuletta; Saakian Sirun; Tatarova Anastasia (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001